1975
DOI: 10.1042/cs0490253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lysine Acetylsalicylate on Biliary Lipid Secretion in Dogs

Abstract: 1. The influence of lysine acetylsalicylate on bile flow, erythritol clearance and bile salt, phospholipid and cholesterol secretion in bile was studied in unanaesthetized dogs fitted with a Thomas duodenal cannula. 2. Lysine acetylsalicylate induced a marked increase in bile flow and a parallel increase in erythritol clearance although the bile salt secretion remained unchanged; this suggests that the compound stimulated the formation of the canalicular (hepatocytic) bile salt-independent fraction of bile flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…This response is less than the 100% choleresis seen in the rhesus monkey (Cooper et al, 1980), and considerably less than the 600% increase in bile flow observed in the dog (Rutherford et al, 1878;Erlinger et al, 1975). No attempt was made in these studies to occlude the distal common bile duct, since it has been shown that a T-tube on dependent drainage produces complete biliary diversion (Rundle et al, 1955 Figure 1 The mean bile flow (ml kg-' 24 h-') in 15 min aliquots during the baseline period and following the administration of 1.8 g oral sodium salicylate.…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations
“…This response is less than the 100% choleresis seen in the rhesus monkey (Cooper et al, 1980), and considerably less than the 600% increase in bile flow observed in the dog (Rutherford et al, 1878;Erlinger et al, 1975). No attempt was made in these studies to occlude the distal common bile duct, since it has been shown that a T-tube on dependent drainage produces complete biliary diversion (Rundle et al, 1955 Figure 1 The mean bile flow (ml kg-' 24 h-') in 15 min aliquots during the baseline period and following the administration of 1.8 g oral sodium salicylate.…”
Section: Methodsmentioning
confidence: 79%
“…Figure 2 The mean bile flow (ml kg-'24 h-')in 15 min aliquots during the baseline period and following the administration of 1.8 oral acetylsalicylate. (Erlinger et al, 1975) and rhesus monkey (Cooper et al, 1980) has shown that the increased bile flow is of canalicular origin. Bile acid secretion was unaltered in man, suggesting that as in the monkey work (Cooper et al, 1980), the salicylate choleresis depends on an increase in the bile-acid independent fraction of canalicular bile flow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, lysine acetyl salicylate has been shown in the dog to reduce the cholesterol saturation of hepatic bile by a reduction in both cholesterol and phospholipid secretion, the bile acid secretion rate remaining unchanged (Erlinger et al, 1975).…”
Section: Introductionmentioning
confidence: 99%